Sex Ratio at Birth and its Determinants: A Cross Sectional Hospital Based Study - Upreti, Purnima; Singh, Rajesh Kumar (National Journal of Community Medicine, 2017)
Introduction: Sex ratio is used to reflect gender equity of the population. Sex ratio in India has shown an upward trend since Census 1991 but during the same period, child sex ratio (0-6 years) has shown a declining trend. Sex ratio at birth affects child sex ratio. This study was planned to determine the sex ratio at birth among deliveries conducted in a government tertiary care hospital of Kumaon region of Uttarakhand. Materials and Methods: A cross-sectional hospital based study conducted in tertiary care centre of Nainital district. Partcipants were selected using systematic random sampling. A pre-tested and pre-structured questionnaire was used to collect information. Data analysed using SPSS version 17 and is presented as numbers, percentages and ratios. Results: Sex ratio at birth was 852 girls to 1000 boys. The highest sex ratio of 1059 was found among the first birth order offsprings which declined to 897,654 and 619 as the birth order increased to second, third and fourth respectively. Sex ratio at birth in rural population was higher (953) than in urban (752). Sex ratio at birth among literate mothers was 857 and in illiterate mothers it was 829. Conclusion: Sex ratio at birth increased with advancing maternal age and literacy status of females whereas it decreased with increase in birth order and number of live females in the families.